A new baseline correction method for near-fault strong-motion records based on the target final displacement. Issue 114 (November 2018) - Lin, Yuanzheng; Zong, Zhouhong; Tian, Shizhu; Lin, Jin
Abstract: Most current baseline correction methods for near-fault ground motion records focus on eliminating and minimizing baseline errors and obtaining true ground motion records that are in accordance with GPS-measured coseismic displacements. Though these methods can recover true ground motions, the single value of ground permanent displacement cannot meet the requirement of seismic response analysis of fault-crossing bridge with the consideration of various levels of relative static displacements. Besides, the corrected final displacements are often too large which will cause an extremely large pseudo-static response and a relatively small dynamic response in bridge structures. To provide across-fault seismic excitations with a reasonable series of final displacements, a new baseline correction scheme based on the target final displacement is proposed in this study, in which an additional offset displacement is introduced based on the Iwan correction scheme. The new baseline correction scheme aims at modifying the pseudo-static displacement of ground motion records to facilitate the agreement between the achieved final displacement and the target final displacement. The correction scheme is then examined in three aspects including time histories, response spectra and bridge responses. The analysis results indicate that sets of the corrected time history records with a large range of final displacements can be well achieved with a minor influence on spectral characteristics. The seismic response analysis of a cable-stayed bridge crossing a dip-slip fault-rupture zone shows that the pseudo-static response can be controlled, meanwhile, the dynamic response remains almost intact by using the new baseline correction scheme. This work can be used as a reference for input excitations of bridge crossing fault-rupture zones. Highlights: A new baseline correction scheme based on the target final displacement is proposed. The pseudo-static component of ground motions can be controlled with the dynamic component remaining intact. Different levels of bridge pseudo-static responses can be achieved without influence on dynamic responses. Provide an approach to simulate the seismic excitations for fault-crossing bridges.